Recent advances on herb‐derived constituents‐incorporated wound‐dressing materials: A review - Krishnan K, Asha; Thomas, Sabu (Polymers for advanced technologies, 2019)
Since ancient times, wound dressings have evolved with persistent and substantial changes. Several efforts have been made toward the development of new dressing materials, which can meet the demanding conditions for the treatment of skin wounds. Currently, many studies have been focused on the production and designing of herb‐incorporated wound dressings. Herb‐derived constituents are more effective than conventional medicines because of their nontoxic nature and can be administered over long periods. Herbal medicines in wound healing provide a suitable environment for aiding the natural course of healing. This review mainly focuses on the diverse approaches that have been developed to produce a wound dressing material, which can deliver herb‐derived bioactive constituents in a controlled manner. This review also discusses the common wound‐dressing materials available, basic principles of wound healing, and wound‐healing agents from medicinal plants.